Multi spiral Computed Tomography Analysis of Chronic Lung Disease Complications in Patients Who Have Undergone Covid-19 Pneumonia (Genius Repository, 2023)
The article provides an analysis of changes in the pulmonary parenchyma in pneumonia caused by a new coronavirus infection in the acute and separated period of the course of the disease. Based on clinical material (60 patients with viral pneumonia, who underwent classical lung radiography and computed tomography at various times of the disease) changes in radiological signs of lung tissue damage were assessed. The dependence of the course and regression of the disease on the degree of lung tissue damage was revealed according to the results of radiography and computed tomography